Inovasi Pembuatan Deterjen Dari Minyak Jelantah - Hartono, Ajeng Ar Rayhaani Cindy; Persada, Asa Aditya; Faiz Musyaffa, Abdurrahman; Rif’at, Bayu Izagy; Arrunata, Daffa Yoganza; Dharmawan, Aditya (Publikasi Indonesia, 2025)
Environmental pollution due to used cooking oil waste and the use of synthetic chemical detergents are serious problems that require innovative solutions. This research aims to develop an environmentally friendly detergent based on used cooking oil as an alternative to conventional detergents. The research method uses a qualitative-descriptive approach with stages of pretreatment of used cooking oil, esterification, transesterification, sulfonation to produce Methyl Ester Sulfonate surfactant, and blending with additives. The results of the study show that JelaWash Detergent products have advantages in removing stains, are biodegradable, produce a long-lasting, gentle scent on clothes and skin. Market analysis of 32 respondents indicated positive acceptance with a preference for liquid detergents of 78 percent. The production capacity is designed to be 50,000 tons per year to meet the gap in Indonesia's detergent needs. The conclusion of the study shows that the use of used cooking oil as a detergent raw material can reduce environmental waste while producing high-quality cleaning products that are economical and sustainable.